Unilateral buccal space masses: a case series - Kumar, Mathangi; Kudva, Adarsh; Vineetha, Ravindranath; Solomon, Monica (Medicine and Pharmacy Reports, 2020)
The head and neck region consists of several potential tissue spaces that are formed by the fascial layer. The buccal space is an area of anatomic significance due to its small size and distribution of adipose tissue. Unilateral buccal space masses often pose a diagnostic challenge owing to the diversity of tissues in the area. Here, we report four such cases of buccal space masses arising from different tissues, which presented as unilateral buccal space swelling. This report also highlights the various causes and the differential diagnoses of unilateral buccal space masses.